'Like Seeing Normal Life'*: children's opera Brundibár in Theresienstadt (1943–1944) and the power of scenographic metaphors. Issue 3 (3rd July 2018) - Pantouvaki, Sofia
ABSTRACT: Czech architect-scenographer František Zelenka was a well-known pre-war designer for the National Theatre in Prague, deported by the Nazis to the Theresienstadt ghetto, a concentration camp in Czechoslovakia, where he participated extensively in the inmates' theatrical activity. Among his works in the ghetto, the children's opera Brundibár, designed and directed by Zelenka, stands out. Brundibár was originally created in 1938 by the Czech Jewish composer Hans Krása and the librettist Adolf Hoffmeister in Prague. Despite the harsh living conditions, 55 performances are known to have been held in Theresienstadt between 1943 and 1944. The staging of Brundibár consisted of visual statements that were an integral part of the scenography and acquired meaning in the context of the ghetto. This article analyses Zelenka's scenography by focusing on the visual metaphors embedded in the stage images he created, and offers an insight on the multiple roles of Brundibár's original scenography and its impact. The aim is to underscore the power in creating and reading scenographic images under coercive conditions, with Brundibár as a paradigmatic example. It demonstrates the ways in which scenography may serve as a reminder of normality for children dealing with issues that cannot otherwise be confronted. The article concludes with a brief commentary on contemporary adaptations of the opera.